Pengembangan Modul Sharaf Dengan Pendekatan Deduktif Di Pondok Modern Madinah Lampung - Mezan Kesuma; Reni Puspita Sari (Universitas Yudharta Pasuruan, 2020)
The objectives of this study are: 1) Developing the sharaf modules with the deductive approach, 2) Knowing the feasibility of the sharaf module with a deductive approach and 3) Knowing the effectiveness of the sharaf module with the deductive approach of class X students in Pondok Modern Madinah Labuhan Maringgai, East Lampung. The development model used the Borg and Gall model with seven stages, namely: preliminary study, research planning, design development, limited trials, limited revision of trial results, wider product testing, and wider revision of trial results. Observing the above statement, the results of this study show that: development of sharaf module with deductive approach is very feasible to use, the results of the material expert validation are 89% and the learning design expert validation results are 86%, the average score of the student's pretest is 54.16 and the posttest value is 84.16. Based on the results of calculations using the SPSS application 24, it is known that the value of to = 15.288 and ttable 1.69913 at a significance level of 5%, so it can be concluded that there is a difference between the pretest value t and posttest grade X students, because t0 15.288> ttable 1.69913, Ha accepted and Ho rejected